PENGARUH KOMPETENSI, KOMUNIKASI, TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL GURU SMP NEGERI DI KABUPATEN PATI - Utami, Utami (Students Journal of Economic and Management, 2012)
The purpose of this research was to investigate the influence of competence and communication toward teacherâs performance with organizational commitmentÂ as mediation variable at secondary high school inÂ Pati regency. There are 206 teachers that used for the research as respondent. This research carried out on July to August 2012. Instrument which is used in this research is by giving list of questions to the respondent. The instrument which is used in this research is computer software SPSS ver.16. program After it has been processed by this program, get the result from validity and reliability test. All variable are valid.With the test Normality, Multicolinierity, and HeteroscedastisityÂ as a whole have no assumption trouble classical. Pursuant to the test above hence it is reachable regression analysis assumption conception the of BLUE Linear or Best Linnier Unbiazed Estimator, hence applying the regression in analyses this research is well implemented.The method used to analyze the data is regression analysis. The result of the first hypotheses test can be proved that the competence variable has positive significant influence to the organizational commitment.The second hypotheses test shows that the competence variable has positive significant influence to the teachers performances. The third hypotheses test shows that the communicationhas positive significant influence to the organizational commitment. The fourth hypotheses test shows that communicationhas positive significant influence to the teachers performances The fifth hypotheses test shows that the organizational commitmenthas positive significant influence to the teachers performance.But as a mediation commitment organizational canât be proved. It shows that cmmitment organizational canâtÂ mediate the influence of both competence and communication toward teachersâ performance Key words:Â competence, communication, organizational commitment, and teacherâsperformance